2022
DOI: 10.1111/cas.15314
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes reveal the dual nature of radiotherapy in tumor immunology

Abstract: There is nearly a century of history behind radiotherapy (RT), which has evolved from discovery to widespread use in clinically significant tumors. Currently, with an estimated 50% of cancer patients receiving RT, radioactive rays such as X-rays are commonly used to weaken the viability of tumor cells before surgery and facilitate radical cure after tumor resection, potentially lowering the risk of cancer recurrence and metastasis. 1 The damage effects of radiation are accomplished by ionizing reactions and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Exosomes take advantage of the targeting of related tumors to reach tumor tissues quickly and precisely, and then increase drug concentrations. The cytotoxic proteins contained in exosomes, such as perforin and Fas/FasL, can cause apoptosis of tumor cells, but do no harm to normal cells ( 103 , 204 ). Indeed, exosomes derived from NK cells are cytotoxic to melanoma cells but have no effect on normal cells ( 205 ).…”
Section: Roles Of Exosomes In the Tmementioning
confidence: 99%
“…Exosomes take advantage of the targeting of related tumors to reach tumor tissues quickly and precisely, and then increase drug concentrations. The cytotoxic proteins contained in exosomes, such as perforin and Fas/FasL, can cause apoptosis of tumor cells, but do no harm to normal cells ( 103 , 204 ). Indeed, exosomes derived from NK cells are cytotoxic to melanoma cells but have no effect on normal cells ( 205 ).…”
Section: Roles Of Exosomes In the Tmementioning
confidence: 99%
“…Exosomes derived from various cells serve an immunosuppressive or immunoenhancing role ( 18 ), and participate in carcinogenesis, proliferation and metastasis ( 19 ), thus playing distinct roles in the abscopal effect. Furthermore, there are alterations in exosome secretion following radiation ( 20 , 21 ). The subsequent sections discuss the mechanisms by which distinct cells produce exosomes after radiation to modify the abscopal effect.…”
Section: Immune Mechanism Of the Abscopal Effectmentioning
confidence: 99%
“…Studies have shown that exosomes induce immunosuppression and immune clearance by analyzing the relationship between exosomes and immunity. As a result, the prognosis of patients is not good 21 . In addition, extensive evidence indicates that the amount of exosomes secreted by tumor cells varies with cellular stress induced by anticancer therapy, leading to the transfer of drug‐resistance phenotypes between BC tumor cells 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the prognosis of patients is not good. 21 In addition, extensive evidence indicates that the amount of exosomes secreted by tumor cells varies with cellular stress induced by anticancer therapy, leading to the transfer of drug‐resistance phenotypes between BC tumor cells. 22 , 23 In tumor progression and therapy, exosomes from BC cells are found to contribute to cancer cell proliferation, metastasis, angiogenesis, chemoresistance, and radioresistance, leading to metastasis of cancer cell lesions to other organs.…”
Section: Introductionmentioning
confidence: 99%